Dinamika Pergolakan Politik di Mesir Abad 20-21 (Sejak Raja Faruq Hingga Muhammad Mursi) - Johan Septian Putra (IAIN Bengkulu, 2022)
Abstract- Egypt since the classical era of Islam to the contemporary era, there have been upheavals that seem endless, especially in the modern era. The political upheaval seems to have become a